P844 Higher proportions of genera and species in the Firmicutes phylum are associated with a healthy pouch compared with patients with chronic pouchitis - Segal,J; Mullish,B; Clark,S; Marchesi,J; Hart,A (Journal of Crohn's and Colitis, 2020)
Abstract Background Studies highlighting changes in bacterial composition in the ileoanal pouch are limited by heterogeneity in analysis techniques and sampling strategies Therefore, caution must be used when interpreting microbiota data. Similar to findings in IBD, a decrease in bacterial diversity and ‘dysbiosis’ are associated with acute and chronic inflammation in the pouch. Changes in Clostridium spp. and E. coli are associated with inflamed pouches and treatment response. This study aimed to compare the bacterial microbiota composition in patients with chronic pouchitis who responded to antibiotics vs. those who did not. Methods Patients with confirmed chronic pouchitis defined by a pouch disease activity score ≥ 7 were treated with antibiotics. If patients were already on antibiotics, they were offered the opportunity to stop. Follow up was at 4 weeks to check clinical status. Patients who came off antibiotics who flared were given the opportunity to restart the antibiotics to prevent deterioration. Patients were analysed as either on antibiotics if they received antibiotics 2 weeks prior to the clinic or off antibiotics if they had stopped all antibiotics 2 weeks prior to follow-up. Stool was collected from patients on follow-up and DNA was extracted from this stool. Sequencing was performed on an Illumina platform. Statistical analysis was performed using STAMP 2.1.3 software with Welch’s two-sided t-test for comparing two groups with false discovery rate correction. Results <j